Integrasi Human Capital dan Etika Kerja Islam dalam Pengembangan SDM Halal di Indonesia : Integration of Human Capital and Islamic Work Ethics in Halal HR Development in Indonesia - Desy Arum Sunarta; Nelia Syafriawati; Siradjuddin, Siradjuddin (Litera Academica Publishing, 2025)
This study aims to analyze the needs and strategies for strengthening human resources (HR) in the halal industry in Indonesia through a library research approach. This study is motivated by the increasing global demand for halal products and services, which requires a competent and certified workforce, and the need to integrate Islamic values ​​into professional practice. The research method uses a systematic literature analysis of national and international scientific sources to identify profiles, competency gaps, training models, and halal HR development policies. The results show that the distribution of the halal workforce in Indonesia is dominated by the food and beverage, pharmaceutical, and tourism sectors, while the availability of halal-certified workers remains far below industry needs. The main factors contributing to the shortage of skilled workers include limited curricula, certification costs, disparities in training infrastructure, and weak collaboration between stakeholders. This study found that competency-based education, link-and-match programs between universities and industry, and the application of digital technologies such as blockchain, artificial intelligence, and e-learning are effective solutions for improving the quality of halal HR. The integration of human capital theory and Islamic work ethics demonstrates that technical and moral competencies play complementary roles in strengthening the competitiveness of the halal workforce and ensuring the sustainability of a values-based economy. In conclusion, strengthening halal human resources in Indonesia should be directed at establishing a collaborative ecosystem between the government, industry, and educational institutions through digitalization strategies, sustainable certification, and the internalization of Islamic work ethics. This study contributes to the development of a scientific framework for halal economic development and offers an empirical basis for formulating national policies toward Indonesia's position as a global halal industry hub.